Evaluations of hydroxyapatite and bioactive glass in the repair of critical size bone defects in rat calvaria - Souza, Eduardo Quintão Manhanini [UNESP] (2020)
To overcome the morbidity of autogenous graft removal and limitations of allogeneic and xenogeneic grafts, a great interest exists in the development of biomaterials of synthetic origin. Objective: The aim of this study was to evaluate the biological behavior of a novel bioactive glass (60% SiO2- 36% CaO-4% P2O5) as bone substitute in critical calvaria defects of rats, in comparison to hydroxyapatite. Methods: Sixty male Wistar rats were divided in three groups, according to the treatment: Control Group (C) - blood clot; Hydroxyapatite (HA) - particulate hydroxyapatite (≤0,5 mm); and Bioactive Glass (BG) - particulate bioactive glass (0.04–1 mm). Results: From the intergroup analysis, it was observed that Group C presented a greater newly formed bone area (NBA) when compared to Groups HA and BG. In addition, Group HA showed higher NBA when compared to Group BG at 30 and 60 days (P < 0.05). Immunohistochemistry revealed that groups HA and BG presented high and moderate osteocalcin immunolabeling respectively. Group HA displayed a greater number of TRAP-positive cells compared to Groups C and BG at 30 and 60 days (p < 0.05). Conclusion: From these results, we can conclude that the resorption rate of hydroxyapatite is higher than the novel bioactive glass, which maintained significant higher volume until the last experimental period. Both of the tested biomaterials acted as osteoconductors during bone repair, and their physical characteristics importantly influenced this process.